FIRST AID MEDICATION AND REMEDIES FOR HEART FAILURE - Akhmedov Shavkatjon Sativoldiyevich (American Journals, 2022)
Dear reader, this article provides information about the drugs used in heart failure, one of the diseases that are currently common ingangj . For most people, Heart Failure is a long-term condition that cannot be treated. But treatment can help keep symptoms under control, possibly for many years. The main treatment options are: healthy lifestyle changes , medications , devices installed on your chest to control heart rhythm, surgery . In most cases, a combination of treatment is required.
Keywords: surgary , drug , digoxin , heart failure , nitrate , pacemakers